AIxIA 2023 - Advances in Artificial Intelligence XXIInd International Conference of the Italian Association for Artificial Intelligence, AIxIA 2023, Rome, Italy, November 6-9, 2023, Proceedings - Basili, Roberto; Lembo, Domenico; Limongelli, Carla; Orlandini, Andrea (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the XXIInd International Conference on AIxIA 2023 - Advances in Artificial Intelligence, AIxIA 2023, held in Rome, Italy, during November 6-10, 2023. The 33 full papers included in this book were carefully reviewed and selected from 53 submissions. They were organized in topical sections as follows: Argumentation and Logic Programming, Natural Language Processing, Machine Learning, Hybrid AI and Applications of AI.
Argumentation and Logic Programming -- ABALearn: An automated logic-based learning system for ABA frameworks -- Deriving Dependency Graphs from Abstract Argumentation Frameworks -- ReConf: An Automatic Context-based Software Reconfiguration Tool for Autonomous Vehicles using Answer-Set Programming -- Mining contrast sequential patterns with ASP -- Ontologies -- An ontological modelling of reason-based preferences -- A Defeasible Description Logic for Abduction -- Ontology-based Data Management in Healthcare: The Case of the Italian Arthroplasty Registry -- Planning -- A Structure-Sensitive Translation from Hybrid to Numeric Planning -- Intrinsically Motivated High-Level Planning for Agent Exploration -- Natural Language Processing -- Mining Argument Components in Essays at Different Levels -- Unraveling ChatGPT: A Critical Analysis of AI-Generated Goal-Oriented Dialogues and Annotations -- Scaling Large Language Models to the Extreme: Neural Semantic Processing of Multiple Tasks in Italian -- Named Entity Recognition and Linking for Entity Extraction from Italian Civil Judgements -- Machine Learning -- CENTAURO: an Explainable AI Approach for Customer Loyalty Prediction in Retail Sector -- Toward Novel Optimizers: A Moreau-Yosida View of Gradient-based Learning -- Mastering the Card Game of Jaipur through Zero-knowledge Self-Play Reinforcement Learning and Action Masks -- Uncovering Bias in the Face Processing Pipeline: An Analysis of Popular and State-of-the-Art Algorithms Across Demographic Groups -- A multi-label classification study for the prediction of long-covid syndrome -- PAUL-2: An Upgraded Transformer-Based Redesign of the Algorithmic Composer PAUL -- Robotics and Perception -- Understanding the Effect of Deep Ensembles in LiDAR-based Place Recognition -- Enanching LiDAR performance: Robust De-skewing Exclusively Relying o n Range Measurements -- Can Existing 3D Monocular Object Detection Methods Work in Roadside Contexts? A Reproducibility Study -- Embedding Shepard's Interpolation into CNN Models for Unguided Depth Completion -- Performance evaluation of depth completion neural networks for various RGB-D camera technologies in indoor scenario -- Hybrid AI -- Inference in Probabilistic Answer Set Programming under the Credal Semantics -- Efficient Modal Decision Trees -- Clique-TF-IDF: A New Partitioning Framework based on Dense Substructures -- Combining Contrastive Learning and Knowledge Graph Embeddings to develop medical word embeddings for the Italian language -- Applications of AI -- Recognizing the Style, Genre, and Emotion of a Work of Art Through Visual and Knowledge Graph Embeddings -- Combining genetic algorithms and temporal constraint satisfaction for recommending personalized tourist itineraries -- Towards Automatic Digitalization of Railway Engineering Schematics -- Election Manipulation in Social Networks with Single-Peaked Agents -- Learning to Prompt in the Classroom to Understand AI Limits: A pilot study.
Keywords: Artificial intelligence; Computer science; Software engineering; Application software; Computers, Special purpose; Compilers (Computer programs).; Artificial Intelligence; Theory of Computation; Software Engineering; Computer and Information Systems Applications; Special Purpose and Application-Based Systems; Compilers and Interpreters